Stress Levels and Seborrheic Dermatitis in the Class of 2020 Medical Students at a University in Indonesia - , Eldy; Darmawan, Hari (Folia Medica Indonesiana, 2023)
Highlights: 1. This research investigated a previously unexplored relationship between stress levels and seborrheic dermatitis in Indonesia. 2. It has been shown that a significant proportion of medical students are susceptible to sleep problems, which can negatively impact their academic performance and mental health. 3. This recent study found that seborrheic dermatitis affects men on average more frequently than women. Abstract : Seborrheic dermatitis is a common skin disease in the form of superficial inflammation with a papulosquamous morphology that often occurs in sebaceous gland-rich areas. Emotional stress is one of the contributing factors to the susceptibility of individuals to seborrheic dermatitis, while lack of sleep is associated with its exacerbation. This study aims to investigate the relationship between stress levels and seborrheic dermatitis cases among the class of 2020 students at the Faculty of Medicine, Universitas Tarumanagara, Jakarta, Indonesia. This study used an analytical-observational approach with a cross-sectional design. The sampling technique used was simple random sampling. The samples were from 114 medical students from the class of 2020 at Universitas Tarumanagara. The data were collected using an online Google Forms questionnaire and a dermatological assessment. The data were analyzed through statistical software, IBM SPSS Statistics for Windows, version 26.0 (IBM Corp., Armonk, N.Y., USA), using the Chi-square hypothesis test. The results showed a significant relationship between sex and seborrheic dermatitis cases (p=0.000). However, there was no significant relationship between stress levels and seborrheic dermatitis cases among the respondents (p=0.591). In conclusion, factors other than stress levels might contribute to the development or exacerbation of seborrheic dermatitis among the participants. Further research is needed to explore the potential underlying mechanisms and additional factors influencing the development and progression of seborrheic dermatitis.